Back-analysis of the water retention curve of a GCL on the wetting path. Issue 5 (16th October 2020) - Tincopa, M.; Bouazza, A.; Rowe, R. K.; Rahardjo, H.
Abstract : A new approach is presented to obtain the water retention curve of a geosynthetic clay liner (GCL) on the wetting path (i.e. when it is hydrating). This approach is based on a back-analysis process using data from a hydration test. The back-analysis method was validated by comparing it to conventional experimental measurement techniques such as vapour equilibrium, chilled-mirror dew point and osmotic techniques as well as published data. This approach is shown to be a viable alternative to quickly identify the retention properties of a GCL on the wetting path.